2005
DOI: 10.2220/biomedres.26.131
|View full text |Cite
|
Sign up to set email alerts
|

Bax/Bcl-2 expression levels of 2-methoxyestradiol-exposed esophageal cancer cells

Abstract: ABSTRACT2-Methoxyestradiol (2ME), an endogenous metabolite of 17β-estradiol, has been reported to play an active role in the induction of apoptosis in both proliferating endothelial and cancer cells. Since it has been indicated that an increased ratio of pro-apoptotic Bax protein to anti-apoptotic Bcl-2 protein expression can be associated with apoptosis, and since the exact action mechanism of 2ME is still not clearly defined and appears to vary according to cell type, the influence of 1 μM 2ME was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…In addition, levels of p53, Bax and p21 were increased, while that of the anti-apoptotic Bcl-2 protein was undetectable in cells treated with 2ME (10). As already mentioned, we have previously demonstrated that the pro-apoptotic Bax/anti-apoptotic Bcl-2 ratio for 2ME-treated WHCO3 cells was 1.45 normalized against Bcl-2 levels, thus favouring induction of apoptosis (14). The increased Cdc2 activity observed in 2ME-treated WHCO3 cells is consistent with the morphological hallmarks of mitotic arrest observed.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, levels of p53, Bax and p21 were increased, while that of the anti-apoptotic Bcl-2 protein was undetectable in cells treated with 2ME (10). As already mentioned, we have previously demonstrated that the pro-apoptotic Bax/anti-apoptotic Bcl-2 ratio for 2ME-treated WHCO3 cells was 1.45 normalized against Bcl-2 levels, thus favouring induction of apoptosis (14). The increased Cdc2 activity observed in 2ME-treated WHCO3 cells is consistent with the morphological hallmarks of mitotic arrest observed.…”
Section: Discussionsupporting
confidence: 55%
“…JNK plays a key role in the phosphorylation and inactivation of the pro-apoptotic protein Bcl-2, thus contributing to the induction of apoptosis (3,5). Furthermore, demonstrated that the Bax/Bcl-2 ratio for 2ME-treated WHCO3 cells was 1.45 normalized against Bcl-2 levels (14). Exposure of human cervical carcinoma cells (HeLa) to 2ME revealed a Bax/Bcl-2 ratio of 1.87 normalized against Bcl-2 levels in these cells, also suggesting that this altered ratio in favor of Bax could lead to the induction of apoptosis in these cells (13).…”
mentioning
confidence: 90%
“…5 Current evidence has suggested that 2-ME is the causative agent leading to an increase in Cdc2 kinase activity, the activation of c-Jun NH 2 -terminal kinase signaling, generation of reactive oxygen species and an altered ratio of Bax/ Bcl-2 in favor of Bax, ultimately culminating into apoptosis. [8][9][10][11] Cell division cycle (Cdc) 2 kinase activity is a cell cycle regulatory component essential for commencement of mitosis, whereas Cdc2 inactivation is needed for mitotic exit. Prolonged Cdc2 activity can sustain the cell in mitosis for an indefinite period until particular conditions are met for mitotic exit.…”
Section: Introductionmentioning
confidence: 99%
“…12 JNK is involved in the phosphorylation and inactivation of Bcl-2, a pro-apoptotic protein, thus contributing to apoptotic induction. 8,9 Nevertheless, apoptotic induction via the extrinsic and intrinsic pathways appears to be dependent on cell type. [13][14][15] It is also known that 2-ME displays a dose-dependent biphasic pattern on cell proliferation at concentrations ranging from 10 À8 to 10 À5 M. Stimulatory effects have been demonstrated at low concentrations of 2-ME and inhibitory effects were observed at high concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6,9,15,16 We have previously confirmed antiproliferative effects and morphological hallmarks of apoptosis in 2 ME-exposed HeLa, as well as WHCO3 squamous oesophageal carcinoma cells and revealed that 2 ME was responsible for an altered ratio of Bax/ Bcl-2 in favour of Bax suggesting that this could lead to the induction of apoptosis in both these cells. 17,18 However, the exact action mechanism of 2 ME is complicated, still not clearly defined and appears to vary according to cell type.…”
Section: Discussionmentioning
confidence: 99%